Models for LRRK2-Linked Parkinsonism. (7th April 2011) - Li, Tianxia; Yang, DeJun; Sushchky, Sarah; Liu, Zhaohui; Smith, Wanli W.
Abstract : Parkinson's disease (PD) is a progressive neurodegenerative movement disorder characterized by the selective loss of dopaminergic neurons and the presence of Lewy bodies. The pathogenesis of PD is not fully understood, but it appears to involve both genetic susceptibility and environmental factors. Treatment for PD that prevents neuronal death progression in the dopaminergic system and abnormal protein deposition in the brain is not yet available. Recently, mutations in the leucine-rich repeat kinase 2 (LRRK2) gene have been identified to cause autosomal-dominant late-onset PD and contribute to sporadic PD. Here, we review the recent models for LRRK2-linked Parkinsonism and their utility in studying LRRK2 neurobiology, pathogenesis, and potential therapeutics.